2022
DOI: 10.1002/aic.17869
|View full text |Cite
|
Sign up to set email alerts
|

Integrating chemical precipitation and membrane separation for phosphorus and ammonia recovery from anaerobic digestate

Abstract: This study focuses on developing and demonstrating feasibility of an integrated chemical precipitation and membrane filtration method for recovering phosphorus (P) and ammonia (NH 3 -N) in two separate streams from anaerobic digestate generated from municipal wastewater. Nutrient recovery from waste streams creates alternative raw material sources of fertilizers and offers opportunities for reduced energy usage and CO 2 emissions compared with their conventional production processes.Using both synthetic and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Piash et al successfully recovered the nutrients phosphorus (P) and ammonia (NH 3 –N) from the anaerobic digestion solution produced by municipal wastewater by using a comprehensive method of chemical precipitation and membrane filtration . Studies have shown that the anaerobic membrane bioreactor (AnMBR)-biochar adsorption-RO process can achieve a 0.503 kWh/m 3 energy offset through biological carbon adsorption to recover ammonia, which is equivalent to reducing 498 g CO 2 /m 3 carbon emissions .…”
Section: Paths For Reducing the Carbon Emissions Of Membrane Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Piash et al successfully recovered the nutrients phosphorus (P) and ammonia (NH 3 –N) from the anaerobic digestion solution produced by municipal wastewater by using a comprehensive method of chemical precipitation and membrane filtration . Studies have shown that the anaerobic membrane bioreactor (AnMBR)-biochar adsorption-RO process can achieve a 0.503 kWh/m 3 energy offset through biological carbon adsorption to recover ammonia, which is equivalent to reducing 498 g CO 2 /m 3 carbon emissions .…”
Section: Paths For Reducing the Carbon Emissions Of Membrane Technologymentioning
confidence: 99%
“…Piash et al successfully recovered the nutrients phosphorus (P) and ammonia (NH 3 −N) from the anaerobic digestion solution produced by municipal wastewater by using a comprehensive method of chemical precipitation and membrane filtration. 93 Studies have shown that the anaerobic membrane bioreactor (AnMBR)-biochar adsorption-RO process can achieve a 0.503 kWh/m 3 energy offset through biological carbon adsorption to recover ammonia, which is equivalent to reducing 498 g CO 2 / m 3 carbon emissions. 94 Shin et al used a fluidized anaerobic membrane bioreactor (AF-MBR) to ammoniate domestic wastewater to produce ammonium-rich effluent, which was then concentrated by the RO process, and finally, concentrated NH 4+ was efficiently recovered by stripping ammonia.…”
Section: Resource Recyclingmentioning
confidence: 99%